The dual association of serum uric acid with the functional outcomes of patients after hip arthroplasty: 1-year follow-up study - Xia, Ming; Han, Yu; Sun, Lihui; Li, Dongbo; Zhu, Chunquan; Li, Dongsong (Frontiers in Surgery, 2025)
BackgroundSerum uric acid (UA) exhibits dual biological roles as both an antioxidant and a pro-oxidant, yet its impact on functional recovery after hip arthroplasty remains unclear. This study investigated the nonlinear relationship between UA levels and 1-year postoperative outcomes in patients undergoing hip arthroplasty.MethodsIn this single-center observational study, 468 hip arthroplasty patients (September 2018–September 2023) were stratified into functional independence (FIM ≥108) and non-independence groups. Serum UA was categorized as low, middle, or high. Functional outcomes were assessed using the UCLA Activity Scale (UCLAAS) and Patient-Reported Satisfaction (PRS) metrics. Restricted cubic splines (RCS) and multivariable regression models evaluated nonlinear and linear associations, adjusted for age, comorbidities, and laboratory parameters.ResultsA U-shaped relationship emerged between UA levels and functional independence (p < 0.01 for nonlinearity). Both low UA (OR = 2.09, 95% CI:1.14–3.85) and high UA (OR = 3.74, 95% CI:1.89–7.41) independently predicted reduced functional independence. Secondary outcomes exhibited domain-specific effects: only high UA correlated with poorer mobility (UCLAAS: β = −0.53, p = 0.015). Multivariable adjustments confirmed the robustness of these associations.ConclusionSerum UA demonstrates a dual, nonlinear association with functional recovery after hip arthroplasty, where extremes perturb redox balance and bone remodeling. Monitoring perioperative UA levels and targeting individualized thresholds may optimize rehabilitation strategies.